Risk of ovarian recurrence after ovarian conservation in early-stage cervical cancer treated with radical surgery: A propensity match analysis. Issue 8 (August 2021) - Bizzarri, Nicolò; Pedone Anchora, Luigi; Kucukmetin, Ali; Ratnavelu, Nithya; Korompelis, Porfyrios; Fedele, Camilla; Bruno, Matteo; Di Fiore, Giacomo Lorenzo Maria; Fagotti, Anna; Fanfani, Francesco; Scambia, Giovanni; Ferrandina, Gabriella
Abstract: Introduction: The primary aim of the present study was to assess the incidence of ovarian metastasis/recurrence and the survival of patients undergoing radical hysterectomy with ovarian conservation (CONSERV) versus oophorectomy (OOPHOR). Secondary aim was to assess the incidence and the characteristics of menopausal symptoms in both groups. Materials and methods: Retrospective, multi-center, observational cohort study including patients <50 years with clinical FIGO 2009 stage IA1-IB1/IIA1 cervical carcinoma, treated by primary surgical treatment between 02/2007 and 07/2019. One-to-one case–control matching was used to adjust the baseline prognostic characteristics in survival analysis. Results: 419 patients were included. 264 in the OOPHOR (63.0%) and 155 (37.0%) in the CONSERV group. Ovarian transposition was performed in 28/155 (18.1%) patients. 1/264 (0.4%) patient had ovarian metastasis from endocervical adenocarcinoma. After propensity-matching, 310 patients were included in the survival analysis (155 per group). 5-year disease-free survival of patients undergoing CONSERV versus OOPHOR was 90.6% versus 82.2%, respectively (p = 0.028); 5-year overall survival was 94.3% versus 90.8%, respectively (p = 0.157). Two patients (1.3%) developed recurrence on the conserved ovary. CONSERV represented an independent protective factor of recurrence (HR:0.361, 95%CI 0.169–0.769; p = 0.008). 28 (20.6%) in the CONSERV group versus 116 (60.4%) in the OOPHOR group complained of menopausal symptoms during follow up (p < 0.001). HRT was prescribed to 12.0% of patients (median HRT time was 20 months). Conclusion: CONSERV was associated with reduced risk of recurrence and menopausal symptoms in early-stage cervical cancer. As the risk of ovarian metastasis and ovarian recurrence is relatively low, CONSERV in pre-menopausal women has to be considered.